Pengaruh Pelatihan dan Pengembangan Sumber Daya Manusia Terhadap Semangat Kerja dan Kinerja Karyawan: Sebuah Systematic Literature Review - Abdul Kholiq; Indra Pujianto; M. Khoirul Afandy; Ingwer Ludwig N; Muhammad Vichi; Yudi Prastyo (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
The increasingly competitive industrial environment requires organizations to continuously improve the quality of their human resources through training and development programs. Although numerous studies have examined the relationship between human resource training, human resource development, employee work enthusiasm, and employee performance, the findings remain fragmented across different industrial sectors and research approaches. Therefore, a comprehensive synthesis is needed to provide a clearer understanding of the relationship among these variables. Keywords: Training, Human Resource Development, Employee Performance, Work Motivation, Systematic Literature Review. This study aims to analyze and synthesize previous research findings regarding the influence of human resource training and development on employee work enthusiasm and performance, as well as to identify consistent patterns that can support strategic human resource management. This research employed the Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines. Literature was collected from Google Scholar, Garuda, SINTA, and Scopus using relevant keywords. The selected articles were screened through inclusion and exclusion criteria, followed by a Quality Assessment process. Data were analyzed using a qualitative descriptive approach through thematic synthesis to identify similarities, differences, and research trends. The findings indicate that human resource training and development consistently have a positive impact on improving employee competencies, motivation, work enthusiasm, productivity, and performance across various organizational sectors. This study proposes a conceptual synthesis demonstrating that training primarily enhances employee competencies, while human resource development strengthens motivation and work enthusiasm. The integration of these two aspects contributes significantly to improving both employee and organizational performance. The findings are expected to serve as a reference for organizations in designing more effective and sustainable human resource development strategies..